2019
DOI: 10.3390/aerospace6100110
|View full text |Cite
|
Sign up to set email alerts
|

Bowtie Methodology for Risk Analysis of Visual Borescope Inspection during Aircraft Engine Maintenance

Abstract: Background—The inspection of aircraft parts is critical, as a defective part has many potentially adverse consequences. Faulty parts can initiate a system failure on an aircraft, which can lead to aircraft mishap if not well managed and has the potential to cause fatalities and serious injuries of passengers and crew. Hence, there is value in better understanding the risks in visual inspection during aircraft maintenance. Purpose—This paper identifies the risks inherent in visual inspection tasks during aircra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
0
13
0
1
Order By: Relevance
“…The fact that a target with the characteristics of a military aircraft can accelerate, turn, execute quick maneuvers, thus turning away from a trajectory with constant speed due to the orders received and due to the atmospheric turbulences, makes the pursuit of a target a difficult task. In order to handle these problems, different approach models have been developed [22]. These models are usually developed based on some statistic models regarding the measurement and processing of noise and target dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that a target with the characteristics of a military aircraft can accelerate, turn, execute quick maneuvers, thus turning away from a trajectory with constant speed due to the orders received and due to the atmospheric turbulences, makes the pursuit of a target a difficult task. In order to handle these problems, different approach models have been developed [22]. These models are usually developed based on some statistic models regarding the measurement and processing of noise and target dynamics.…”
Section: Methodsmentioning
confidence: 99%
“…As per the ICAO Safety Management Manual, a hazard is defined as "condition, object, process or activity with the potential of causing harm or damage, including injuries to personnel, damage to equipment, properties or environment, loss of material or reduction in ability to perform a prescribed function" [27]. Previous work showed that Bowtie is a useful tool for such risk assessments, but has some limitations, such as the process of constructing a Bowtie being ad hoc and arbitrary [7]. It highly depends on expert knowledge and the personal preferences and outlook of the analyst [4,[20][21][22].…”
Section: Existing Approaches Constructing a Bowtie Diagrammentioning
confidence: 99%
“…The next step is defining the top event, which describes the release or loss of control over the hazard. "It has not caused any damage or negative impact yet, but can lead to undesired outcomes if all prevention barriers fail" [7]. The terminology of the 'top event' originates form the fault tree analysis.…”
Section: Existing Approaches Constructing a Bowtie Diagrammentioning
confidence: 99%
See 2 more Smart Citations